Bioactive compounds, phenolic profile, antioxidant capacity and effectiveness against lipid peroxidation of cell membranes of Mauritia flexuosa L. fruit extracts from three biomes in the Ecuadorian Amazon - Reinier Abreu-Naranjo; Jonathan G. Paredes-Moreta; Genoveva Granda-Albuja; Gabriel Iturralde; Ana M. González-Paramás; José M. Alvarez-Suarez (Heliyon, 2020)
The bioactive compounds, total antioxidant capacity and protective effect against lipid oxidative damage of red blood cell (RBC) membranes of Mauritia flexuosa L. extracts from three altitude levels (low, middle and high zones) were analyzed. The identification of the main polyphenols in the fruit was performed using High Performance Liquid Chromatography/Electrospray Ionization Tandem Mass Spectrometry analysis, while High-Performance Liquid Chromatography - Diode Array Detector was applied for the vitamin C and carotenoid analysis. The ability of the extracts (methanolic, free polyphenols and bound polyphenols) to protect RBC membranes against oxidative destruction was assessed utilizing the thiobarbituric acid reactive substance assay (TBARS) assay. Among the 14 phenolic compounds identified, quercetin glycosides were the most predominant ones. The fruit from the middle altitude zone showed higher vitamin C and lutein contents than those from the low and high areas, whilst higher values of β-Carotene were obtained in M. flexuosa L. from the low zone. The contents of flavonoids and total polyphenols were lower in fruit from the low zone, whilst the fruit from the middle zone had the highest values. Similar results were observed in the results of the antioxidant capacity assays. However, a significant difference was not found in the protective effect of the extracts from the three altitude zones against lipid peroxidation in RBC membranes.